Role of Family Communication and Boarding School System in Forming Child Independence - Pabundu, Devina Dhea; Ramadhana, Maulana Rezi (Mediator: Jurnal Komunikasi, 2023)
Early adolescence is a phase that a person goes through at the age of 12-15 and is very vulnerable to emotional changes that will further affect other aspects of life, including independence. There are several factors that support the efforts in preparing independent adolescents. The role of the family, especially parents, is essential in shaping children's character, particularly for children who are starting their early adolescent phase. Independence can also be fulfilled through the educational environment in boarding schools. Role of family communication and boarding school system in forming child independence study uses a quantitative approach with a correlational method type on 222 children who attended Islamic boarding schools. The measuring tools used in this study, the Parent-Child Communication Questionnaire and Independence Questionnaire. The results showed a significant relationship between conversation orientation on the dimensions of self-help, responsibility, socialization, and initiative and a significant relationship between conformity orientation on two dimensions, responsibility and initiative. The implications of this study showed that the communication pattern of parents in boarding schools is laissez-faire; they entrust their children's educational problems to particular institutions, such as boarding schools. The Laissez-Faire type has a low conversational orientation and conformity, which is in line with the results of research that not all variables of independence are significant.